2016
DOI: 10.1093/nar/gkw818
|View full text |Cite
|
Sign up to set email alerts
|

A Pap1–Oxs1 signaling pathway for disulfide stress inSchizosaccharomyces pombe

Abstract: We describe a Pap1–Oxs1 pathway for diamide-induced disulfide stress in Schizosaccharomyces pombe, where the nucleocytoplasmic HMG protein Oxs1 acts cooperatively with Pap1 to regulate transcription. Oxs1 and Pap1 form a complex when cells are exposed to diamide or Cd that causes disulfide stress. When examined for promoters up-regulated by diamide, effective Pap1 binding to these targets requires Oxs1, and vice versa. With some genes, each protein alone enhances transcription, but the presence of both exerts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 32 publications
(40 reference statements)
2
39
0
Order By: Relevance
“…To test whether any of these seven amino acid substitutions introduced into the full-length Oxs1 protein would affect its subcellular localization, each variant was fused to the C terminus of GFP. As described previously (He et al 2017), GFP-Oxs1 fluorescence can be observed in the nucleus upon treatment with diamide but not in the absence of stress ( Figure 4A). For the substitution mutants in the absence of diamide, only GFP-Oxs1 A110V , GFP-Oxs1 L113F , or GFP-Oxs1 S115G , like the GFP-Oxs1 control, retained the ability to be excluded from the nucleus (Figure 4Ba-c).…”
Section: Nuclear Exclusion Capability Associated With Diamide Tolerancesupporting
confidence: 82%
See 4 more Smart Citations
“…To test whether any of these seven amino acid substitutions introduced into the full-length Oxs1 protein would affect its subcellular localization, each variant was fused to the C terminus of GFP. As described previously (He et al 2017), GFP-Oxs1 fluorescence can be observed in the nucleus upon treatment with diamide but not in the absence of stress ( Figure 4A). For the substitution mutants in the absence of diamide, only GFP-Oxs1 A110V , GFP-Oxs1 L113F , or GFP-Oxs1 S115G , like the GFP-Oxs1 control, retained the ability to be excluded from the nucleus (Figure 4Ba-c).…”
Section: Nuclear Exclusion Capability Associated With Diamide Tolerancesupporting
confidence: 82%
“…In vitro GST pull-down assays were performed as in He et al (2017). His-Pap1 was incubated with GST beads bound to GST or GST fused to GFP as control, GST fused to Oxs1, GST fused to Oxs1 variants with mutations in the NES, or to GST fused with an Oxs1-truncated peptide.…”
Section: In Vitro Gst Pull-down Assaymentioning
confidence: 99%
See 3 more Smart Citations